Problems in Teaching Tourism Register for English Specific Purposes (ESP) Class - Claria, Dewa Ayu Kadek; Warmadewi, A.A. Istri Manik (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2020)
The purpose of this research was to find out the problems in teaching tourism register in English Specific Purposes (ESP) class. Students are expected to know the tourism register as the new group of vocabulary and being able to use them in the related field. When the tourism register is implanted in the course, there were some problems appeared. By reading many literatures related to the topic, the problems can be investigated. It was found that there are some problems which influenced the teaching method in ESP class. The problems can be generalized into two main problems namely; the lecturer’s problems and student’s problems. The lecturer’s problems consist of ineffective teaching and learning method includes the design material which is not fit enough for some ESP students. The student’s problems are divided into the student English proficiency, lack of vocabulary, lack of motivation and basic skill in reading, writing, listening and speaking skills.